Normal Hearing Ability but Impaired Auditory Selective Attention Associated with Prediction of Response to Donepezil in Patients with Alzheimer’s Disease - Yoshitaka Ouchi; Kenichi Meguro; Kyoko Akanuma; Yuriko Kato; Satoshi Yamaguchi (Behavioural Neurology)
Background. Alzheimer’s disease (AD) patients have a poor response to the voices of caregivers. After administration of donepezil, caregivers often find that patients respond more frequently, whereas they had previously pretended to be “deaf.” We investigated whether auditory selective attention is associated with response to donepezil. Methods. The subjects were40 AD patients, 20 elderly healthy controls (HCs), and 15 young HCs. Pure tone audiometry was conducted and an original Auditory Selective Attention (ASA) test was performed with a MoCA vigilance test. Reassessment of the AD group was performed after donepezil treatment for 3 months. Results. Hearing level of the AD group was the same as that of the elderly HC group. However, ASA test scores decreased in the AD group and were correlated with the vigilance test scores. Donepezil responders (MMSE 3+) also showed improvement on the ASA test. At baseline, the responders had higher vigilance and lower ASA test scores. Conclusion. Contrary to the common view, AD patients had a similar level of hearing ability to healthy elderly. Auditory attention was impaired in AD patients, which suggests that unnecessary sounds should be avoided in nursing homes. Auditory selective attention is associated with response to donepezil in AD.